Employee Information Payment System in Pt. Meco Inoxprima Sidoarjo (case Study: PT. Meco Inoxprima) - Azis Abdul Ardiansyah; Syariful Alim; Fardanto Setyatama (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
At present, the data and information processing requires speed and accuracy. Based on the knowledgewe are studying, to Obtain it must be supported by an Appropriate and efficient information technology andrelevant to its application. PT. Meco Inoxprima is one of the company's processing equipment and factories thatwill the make the payroll process to its employees and the make payroll report as accountability to themanagement of the company. The process of recording and calculation of Salaries applied by the company isstill less effective Because The process is done only a few through the system that causes the salary process isOften too late. In solving the problem then the authors designed a payroll information system employees. In thisdesign, the author uses the NetBeans IDE 8.2 programming language, with the database format using mysql, andthe results of the reports using iReport NetBeans IDE 8.2. The results of this study Obtained a java-basedpayroll information system employees. Information Obtained from this system are: employee self-Data related topayroll and employee salary slips.